2015
DOI: 10.5539/res.v7n5p10
|View full text |Cite
|
Sign up to set email alerts
|

Study of University Students’ Social Competence Development

Abstract: The aim of the study was to investigate and diagnose university students' social competence, as well as to develop and implement the program, containing a variety of forms and methods of formation of university students' social competence. For this purpose, there was carried out the experiment, which involved 150 students of Kazan Federal University. The experiment applied complex diagnostic techniques to identify the level of social intelligence, empathic abilities, conflict-resolution strategies. On the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…It has also been found that people who are able to communicate, co-operate, handle conflicts, achieve goals, adapt easily, develop the initiative and to take responsibility are regarded as socially competent (Valeeva and Karimuva, 2014). A study by Padilla-Walker et al (2015) also found association between friendship, sympathy and pro-social behaviour towards friends and Parfilova and Karimova (2015) discovered that socially competent graduates are able to work with others, listen, understand and empathize with others and demonstrate good behaviour in challenging situations. These discoveries are indicative of the fact that social competence is a veritable trait for human development.…”
Section: Relevance Of Social Competencementioning
confidence: 95%
See 1 more Smart Citation
“…It has also been found that people who are able to communicate, co-operate, handle conflicts, achieve goals, adapt easily, develop the initiative and to take responsibility are regarded as socially competent (Valeeva and Karimuva, 2014). A study by Padilla-Walker et al (2015) also found association between friendship, sympathy and pro-social behaviour towards friends and Parfilova and Karimova (2015) discovered that socially competent graduates are able to work with others, listen, understand and empathize with others and demonstrate good behaviour in challenging situations. These discoveries are indicative of the fact that social competence is a veritable trait for human development.…”
Section: Relevance Of Social Competencementioning
confidence: 95%
“…These discoveries are indicative of the fact that social competence is a veritable trait for human development. This assertion finds expression in the following that social competence is increasingly important predictors of success in school (Roma and Bakashi, 2015), for successful work (Parfilova and Karimova, 2015) and in society (Roma and Bakashi, 2015). On their part, Padilla-Walker et al (2015) regarded social competence as a crucial factor in promoting social interactions and social Kuranchie and Addo 11 acceptance from others and friendships.…”
Section: Relevance Of Social Competencementioning
confidence: 99%
“…Jung (2014) and Rawles (2016) in corroborating the findings of this study, indicated in their respective studies that, pupils between the ages of 13-17 are mostly socially competent and exhibit decent social communication skills, establishing and maintaining a positive relationship with others. However, Parflova and Karimova (2015) in their study had a contradictory finding. Their study revealed that pupils at this age suffer from identity crises which makes it difficult for them to develop the needed social skills.…”
Section: Table 2 Social Development Of Pupilsmentioning
confidence: 85%
“…This finding is interesting because the same number of pupils were found to be socially developed. Socially developed people according to Padilla-Walker et al (2015) and Parflova and Karimova (2015) possess skills that enable them to excel in every endeavour they find themselves. On this note, one would have expected that the pupils would perform well academically.…”
Section: What Is the Academic Performance Of Jhs Pupils In The Assin ...mentioning
confidence: 99%
“…There are the following among them: integration of vocational and common cultural training of specialists along with their personal qualities development, aspiration to self-realization, creative selfexpression; move to creation of curricula in a block-based way with a wide choice of elective courses, rating system of knowledge evaluation, a wide range of opportunities for independent deepening of specialization; introduction of open systems of intensive training in educational process, etc. (Valeeva&Karimova, 2013;Parfilova& Karimova, 2015;Sakhieva et al, 2015).…”
Section: Tendencies In Organizational-content Updating Of Educational Processmentioning
confidence: 99%